Extreme evolutionary stability of conserved non-protein coding element of baculovirus genome - Makarenko, V.E.; Kikhno, I.M.; Kashuba, V.I. (Вiopolymers and Cell, 2016)
Aim. To estimate a level of evolutionary stability of the baculovirus conserved non protein-coding element (CNE) playing an essential role in baculovirus pathogenesis. Methods. NCBI-BLAST was applied to identify the orthologous sequences in genomes of 50 alphabaculoviruses. The orthologous sequences were aligned by using ClustalW software. Alistat tool was applied to obtain the pairwise percent identity ( %ID) matrix data. Results. An average pairwise ID value (73 %) calculated for the 1225-member sample was shown to be comparable with those of coding parts of the most conserved baculovirus genes polh and pif2 as well as with those of the polh and p18 promoter regions which are the most conserved representatives of a small group of the evolutionary stable promoter regions of the alphabaculovirus late genes. Conclusion. CNE is one of the most conserved elements of the alphabaculovirus genome. Мета. Визначити рівень еволюційної стабільності CNE (conserved non protein-coding element) – некодуючого функціонального елементу бакуловірусного геному, що грає виключну роль у патогенезі бакуловірусів. Методи. Для ідентифікації ортологічних послідовностей в геномах 50 альфабакуловірусів застосовували NCBI-BLAST. Ортологічні послідовності вирівнювали за допомогою алгоритму вирівнювання ClustalW. Отримували матрицю значень відсотків ідентичності (percent identity, %ID) для попарних порівняннь за допомогою програми Alistat. Результати. Середній рівень ID (73 %), розрахований для 1225-членної вибірки, виявився порівнюваним з такими показниками кодуючих послідовностей найконсервативніших бакуловірусних генів polh та pif2, а також з показниками промоторних ділянок polh та p18, що є найконсервативнішими представниками невеликої групи еволюційно стабільних промоторних ділянок пізніх генів. Висновки. CNE є одним з найконсервативніших елементів геномів альфабакуловірусів. Цель. Определить уровень эволюционной стабильности CNE (conserved non protein-coding element) – некодирующего функционального элемента бакуловирусного генома, который играет исключительную роль в патогенезе бакуловирусов. Методы. Для идентификации ортологичных последовательностей в геномах 50 альфабакуловирусов применяли NCBI-BLAST. Ортологичные последовательности выравнивали при помощи алгоритма выравнивания ClustalW. Получали матрицу значений процентов идентичности (percent identity, %ID) для попарных сравнений при помощи программы Alistat. Результаты. Средний уровень ID (73 %), рассчитанный для 1225-членной выборки, является сравнимым с таковыми показателями кодирующих последовательностей наиболее консервативных бакуловирусных генов polh и pif2, а также с показателями промоторных участков polh и p18, которые являются самыми консервативними представителями небольшой группы эволюционно стабильных промоторных участков поздних генов. Выводы. CNE является одним из наиболее консервативных элементов геномов альфабакуловирусов.